Sugar-Sweetened Beverage Attitudes and Consumption During the First 1000 Days of Life - Woo Baidal, Jennifer A. (Am J Public Health, 2018)
Objectives. To examine the relationship of parental sugar-sweetened beverage (SSB) attitudes with SSB consumption during the first 1000 days of life—gestation to age 2 years. Methods. We studied 394 Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)–enrolled families during the first 1000 days of life in northern Manhattan, New York, in 2017. In regression models, we assessed cross-sectional relationships of parental SSB attitude scores with habitual daily parent SSB calories and infant SSB consumption, adjusting for demographic and socioeconomic characteristics. Results. Each point higher parental SSB attitude score was associated with lower parental SSB consumption (–14.5 median kcals; 95% confidence interval [CI] = −22.6, −6.4). For infants, higher parental SSB attitude score was linked with lower odds of infant SSB consumption (adjusted odds ratio [AOR] = 0.84; 95% CI = 0.71, 0.99), and adjustment for socioeconomic factors slightly attenuated results (AOR = 0.85; 95% CI = 0.71, 1.02). Conclusions. During the first 1000 days of life, greater negativity in parental attitudes toward SSB consumption was associated with fewer parental calories consumed from SSBs and lower likelihood of infant SSB consumption. Public Health Implications. Parental attitudes toward SSBs should be targeted in future childhood obesity interventions during pregnancy and infancy.